2002
DOI: 10.1152/ajpendo.00353.2001
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-specific regulation of proteasome-mediated proteolysis of estrogen receptor-α

Abstract: Ligand-specific regulation of proteasome-mediated proteolysis of estrogen receptor-␣. Am J Physiol Endocrinol Metab 282: E891-E898, 2002. First published December 18, 2001 10.1152/ajpendo.00353.2001.-Proteasome-mediated proteolysis modulates the cellular concentration of estrogen receptor-␣ (ER␣) and is induced by treatment of cells with 17␤-estradiol. Herein, we show that multiple receptor agonists, including 17␣-estradiol and estriol as well as the antagonist ICI-182780, stimulate proteasome-dependent prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 42 publications
11
65
0
Order By: Relevance
“…4G). Estradiol-mediated down-regulation of maxi-K channel membrane expression may indicate that proteasome-dependent proteolytic degradation may be responsible, since this mechanism is involved in down-regulation of the ligand-activated ER␣ (24). According to this hypothesis, inhibition of the proteasome complex would stabilize the maxi-K channel protein on the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4G). Estradiol-mediated down-regulation of maxi-K channel membrane expression may indicate that proteasome-dependent proteolytic degradation may be responsible, since this mechanism is involved in down-regulation of the ligand-activated ER␣ (24). According to this hypothesis, inhibition of the proteasome complex would stabilize the maxi-K channel protein on the cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Ligand binding is required for the estradiol receptor to be targeted to, and degraded by, proteasomes (24,27). It has also been reported that the estrogen sensitivity of the maxi-K channel is conferred by its accessory ␤1-subunit (14,15).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of ERα was higher in the E 2 and OHT treated cells, and these ligands have been reported to stabilize ERα protein in other systems [45]. We saw a dramatic loss of ERα protein upon ICI treatment, and this ligand has been reported to promote rapid degradation of the receptor in other systems [46,47]. A non-specific protein band (NS) was used as a loading control for mES cell samples.…”
Section: Mechanism Of Pr Gene Induction During Differentiation Inducementioning
confidence: 92%
“…Treatment of ER a-transfected HeLa cells with the proteasome inhibitor, MG132, stabilized ER a levels but impaired ER a-mediated transcription (Lonard et al, 2000). Mutations in helix 12 of ER a, the critical core of the AF-2 function of the receptor that interacts with transcriptional coactivators such as SRC-1, abolished ligand-mediated degradation and transactivation of the receptor (Lonard et al, 2000;Preisler-Mashek et al, 2002). Interestingly, some receptor antagonists including tomoxifen, which is an antiestrogen used in breast cancer therapy, stimulate proteasome-dependent proteolysis of ER a (Preisler-Mashek et al, 2002, Pearce et al, 2003.…”
Section: Estrogen Receptor Signaling Regulated By Ubiquitinationmentioning
confidence: 99%
“…Mutations in helix 12 of ER a, the critical core of the AF-2 function of the receptor that interacts with transcriptional coactivators such as SRC-1, abolished ligand-mediated degradation and transactivation of the receptor (Lonard et al, 2000;Preisler-Mashek et al, 2002). Interestingly, some receptor antagonists including tomoxifen, which is an antiestrogen used in breast cancer therapy, stimulate proteasome-dependent proteolysis of ER a (Preisler-Mashek et al, 2002, Pearce et al, 2003. It is likely that the antiestrogen effect of such ligand antagonists is, at least in part, mediated by the modification of ubiquitin-proteasome-dependent degradation of ER a.…”
Section: Estrogen Receptor Signaling Regulated By Ubiquitinationmentioning
confidence: 99%